Complex treatment of candidiasis of the oral mucosa in drug dependent patients - Tymofieiev, O.; Ushko, N.; Chichua, Zurab; Chichua, Nino (Actual Dentistry, 2018)
Purpose: to determine the effectiveness of the use of the complex antibacterial action drugs «Macmiror» and «Macmiror Complex» for the treatment of candidiasis esions of the oral mucosa in drug dependent patients. Methods: a complex clinical and microbiological examination of 81 drug dependent patients aged 19 to 38 years with candidiasis lesions of the oral mucosa was xamined (49 patients – the first group, 32 – the second group). Results: based on our studies, we can state that the complex use of «Macmiror» and «Macmiror Complex» is one of the most effective medicines used to treatment andidadiasis infections of the oral mucosa in drug dependent patients. The use of this set of drugs can completely eliminate all microflora, which is found in pathological oci in the candidiasis of the oral mucosa in patients who use drugs. Conclusion. The antifungal drug «Macmiror» and «Macmiror Complex» is recommended for dentists and maxillofacial surgeons for the treatment of fungal infections candidiasis) of the mucosa in patients who use drugs, as well as in HIV-infected patients. Key words: mucous membrane, candidiasis of the oral cavity, drug addiction, microflora, inflammation, antifungal drugs, Macmiror, Macmiror Complex.